Implementation of Instructional Leadership in Managing Student Academic Achievement - Damayanti, Emy; Nurkolis, Nurkolis; Muhtarom, Muhtarom (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2026)
This study aims to describe the implementation of instructional leadership by the principal in managing student learning achievement at State Elementary School 2 Kutoharjo, Kaliwungu District, Kendal Regency. This study employed a qualitative approach with a descriptive case study design to obtain an in-depth understanding of instructional leadership practices in the school context. The data consisted of primary and secondary data. Primary data were obtained through semi-structured interviews and participant observations involving the principal, teachers, and students, while secondary data were obtained from school documents, including educational reports, learning achievement records, supervision documents, and documentation of student achievement. Data were collected through semi-structured interviews, participant observation, and documentation. Data analysis employed the Miles and Huberman interactive model, consisting of data collection, data condensation, data display, and conclusion drawing. The findings indicate that instructional leadership at State Elementary School 2 Kutoharjo was implemented systematically through the POAC management functions: Planning, Organizing, Actuating, and Controlling. Planning involved participatory formulation of the school's vision and learning objectives based on educational report data and previous achievement records. Organizing focused on proportional teacher assignment, coordination, and creative management of facilities and infrastructure. Actuating included learning supervision, motivation, teacher and student coaching, and achievement-oriented programs. Controlling involved continuous evaluation and follow-up through remedial and enrichment programs. The consistent integration of POAC functions contributed to improved student achievement at district and provincial levels during 2023–2025. This study provides theoretical and practical implications for strengthening instructional leadership in elementary education.